Hydrophobic and Optical Properties of P(VDF-HFP) Nanofiber Filled with Nickel (II) Chloride Hexahydrate for Dye-Sensitized Solar Cells Application - Tohluebaji, Nikruesong; Siri, Ratchanewan; Muensit, Nantakan; Putson, Chatchai; Channuie, Phongpichit; Porrawatkul, Paweena; Yuennan, Jureeporn (Trends in Sciences, 2024)
This study explores the enhancement of dye-sensitized solar cells (DSSCs) by incorporating nickel chloride hexahydrate (NiCl2ꞏ6H2O) into poly(vinylidene fluoride hexafluoropropylene) (P(VDF-HFP)) nanofiber mats. The addition of NiCl2ꞏ6H2O significantly improves the nanofiber morphology, leading to smoother, bead-free fibers with reduced diameters. Enhanced hydrophobicity is achieved through increased water contact angles and lower surface energy. Crystallinity and mechanical properties, including tensile stress and Young’s modulus, are also improved, though ductility is reduced. Optical properties benefit from additional absorbance features due to Ni2+ ions, while electrical conductivity increases, forming conductive pathways that facilitate electron transport. These modifications collectively suggest that NiCl2ꞏ6H2O/P(VDF-HFP) composite nanofibers can substantially improve DSSC performance by offering superior mechanical strength, hydrophobicity, and electrical conductivity. HIGHLIGHTS The study investigates the impact of incorporating nickel chloride hexahydrate (NiCl₂·6H₂O) into poly(vinylidene fluoride hexafluoropropylene) (P(VDF-HFP)) nanofiber mats to enhance dye-sensitized solar cells (DSSCs). Key findings include: Improved Nanofiber Morphology: NiCl₂·6H₂O leads to smoother, bead-free nanofibers with smaller diameters. Enhanced Hydrophobicity: The composite fibers exhibit higher water contact angles and lower surface energy. Better Mechanical Properties: Increased crystallinity, tensile stress, and Young’s modulus, although with reduced ductility. Enhanced Optical and Electrical Properties: Ni²⁺ ions add absorbance features, and electrical conductivity improves, aiding electron transport. GRAPHICAL ABSTRACT